2021
DOI: 10.3389/fphys.2021.742922
|View full text |Cite
|
Sign up to set email alerts
|

Microplastics-Induced Eryptosis and Poikilocytosis in Early-Juvenile Nile Tilapia (Oreochromis niloticus)

Abstract: This study aims to assess the impact of microplastics (MPs) on erythrocytes using eryptosis (apoptosis) and an erythron profile (poikilocytosis and nuclear abnormalities), considered to be novel biomarkers in Nile tilapia (Oreochromis niloticus). In this study, four groups of fish were used: The first was the control group. In the second group, 1 mg/L of MPs was introduced to the samples. The third group was exposed to 10 mg/L of MPs. Finally, the fourth group was exposed to 100 mg/L of MPs for 15 days, follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 62 publications
1
17
0
Order By: Relevance
“…In this study, the gill tissue showed deformation, including shortening of the SL, fusion and vacuolation of the interlamellar epithelium, displacement of epithelial cells, vacuolation of the blood capillaries, severe edema, hyperemia, and lifting of the epithelium. These alterations were similarly reported in carp exposed to lead acetate (Mustafa et al, 2017), catfish exposed to 4-NP (Sayed et al, 2012), Oreochromis niloticus exposed to MPs (Hamed et al, 2021), and other types of fish exposed to different contaminants (Cengiz and Unlu, 2006;Figueiredo-Fernandes et al, 2007;Farrell et al, 2010;Hadi and Alwan, 2012;Sayed et al, 2020). The gills of teleost fishes can be damaged by exposure to high concentrations of different contaminants (Dutta et al, 1996;Wendelaar Bonga, 1997).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…In this study, the gill tissue showed deformation, including shortening of the SL, fusion and vacuolation of the interlamellar epithelium, displacement of epithelial cells, vacuolation of the blood capillaries, severe edema, hyperemia, and lifting of the epithelium. These alterations were similarly reported in carp exposed to lead acetate (Mustafa et al, 2017), catfish exposed to 4-NP (Sayed et al, 2012), Oreochromis niloticus exposed to MPs (Hamed et al, 2021), and other types of fish exposed to different contaminants (Cengiz and Unlu, 2006;Figueiredo-Fernandes et al, 2007;Farrell et al, 2010;Hadi and Alwan, 2012;Sayed et al, 2020). The gills of teleost fishes can be damaged by exposure to high concentrations of different contaminants (Dutta et al, 1996;Wendelaar Bonga, 1997).…”
Section: Discussionmentioning
confidence: 66%
“…Microplastics and 4-NP may accumulate in the liver tissue causing hepatic necrosis and degenerative changes. Histopathology studies indicate that hepatocyte damage is related to energy reductions and metabolic disturbances, microtubule disaggregation, protein synthesis inhibition, and an increase in hepatic red blood cell production (Laureń et al, 1990;da Costa Araujo et al, 2020;Hamed et al, 2021). In the liver, PE plastics may block hepatic capillaries, causing sinusoidal dilatation (Brancatelli et al, 2018;Hamed et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…This may cause inhibition of growth and development ( Koelmans et al, 2014 ) and energy deficiency ( Galloway 2015 ). Among the cellular impacts were modifications to immunological responses, the lysosomal compartment, peroxisome proliferation, antioxidant system, neurotoxic effects, and the start of genotoxicity ( Avio et al, 2015 ; Hamed et al, 2019 ; Hamed et al 2020 ; Hamed et al 2021 ; Sayed et al, 2021 ; Ammar et al, 2022 ; Sayed et al, 2022 ; Sayed et al, 2022 ). Microplastic-induced reactive oxygen species (ROS) has been shown to be an inducer of oxidative stress in some marine organisms ( Wright et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Also, the rise in the morphological distortions of erythrocytes in catfish under disclosure to UVA was investigated (Osman et al, 2019). Even more, exposure to heavy can cause damage and mutation in DNA, reflecting in the quality of micronucleus and other alterations in erythrocytes, as previously studied (Osman et al, 2019;Soliman et al, 2019;Sayed et al, 2021a;Sayed et al, 2021b;Hamed et al, 2021;Soliman et al, 2021;Hamed et al, 2022). In another study conducted by Trifuoggi et al (2017), a group of chlorides of 7 REEs were tested on two sea urchin species showed developmental defects and cytogenetic anomalies.…”
Section: Discussionmentioning
confidence: 95%